Damaged road detection using Image Processing and Deep Learning - Swadesh, Shimran Mahbub; Ahmed, Rifat; Hossain, MD. Imran; Rahman, MD. Raihan (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.